2018
DOI: 10.3171/2017.12.peds17404
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-approach single-level apical spinal osteotomy in pediatric patients for severe rigid kyphoscoliosis: long-term clinical and radiological outcomes

Abstract: OBJECTIVESpinal osteotomy in pediatric patients is challenging due to various factors. For correction of severe rigid kyphoscoliosis in children, numerous techniques with anterior or posterior or combined approaches, as well as multilevel osteotomies, have been described. These techniques are associated with prolonged operative times and large amounts of blood loss. The purpose of this study was to evaluate the clinical and radiologically confirmed efficacy of a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Rajasekaran et al, in a series involving 17 patients, reported that the average kyphosis improved from 69.2° preoperatively to 32.4° postoperatively by closing the opening wedge osteotomy [ 46 ]. Researchers employed a novel technique of apical spinal osteotomies through a posterior approach in rigid severe kyphoscoliosis and found excellent results, validating its use in children under 14 years of age [ 55 ].…”
Section: The Presentmentioning
confidence: 99%
“…Rajasekaran et al, in a series involving 17 patients, reported that the average kyphosis improved from 69.2° preoperatively to 32.4° postoperatively by closing the opening wedge osteotomy [ 46 ]. Researchers employed a novel technique of apical spinal osteotomies through a posterior approach in rigid severe kyphoscoliosis and found excellent results, validating its use in children under 14 years of age [ 55 ].…”
Section: The Presentmentioning
confidence: 99%
“…The definitive treatment of the congenital kyphoscoliosis caused by HV should include removal of HV. Recently, HV excision via posterior approach or single level apical osteotomy in pediatrics has been reported as the choice of treatment with successful results [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The de nitive treatment of the congenital kyphoscoliosis caused by HV should include removal of HV. Recently, HV excision via posterior approach or single level apical osteotomy in pediatrics has been reported as the choice of treatment with successful results [10][11][12].…”
Section: Introductionmentioning
confidence: 99%